EARLY COMPLICATIONS OF SIMPLE ANTERIOR CERVICAL DISCECTOMY - Khan, Zahid; Sharafat, Seema; Ali, Mumtaz (Journal of Postgraduate Medical Institute, 2012)
Objective: To analyze early complications after simple anterior cervical discectomy. Methodology: This descriptive study was conducted at the department of Neurosurgery, Post-graduate medical institute, Lady Reading Hospital Peshawar from January 2009 to December, 2010. Ninety five (95) consecutive patients who underwent single level anterior cervical discectomy without bone grafting for degenerative cervical disc herniation were included in the study irrespective of their age and gender. The patients were observed for post-operative complications for a period of 8weeks after surgery. The patients were observedfor complications during hospital stay, 1stfollow up at 2 weeks and 2ndfollow up after 8 weeks of surgery. Results: Out of 95 cases, 67.4% (n=64) were malesand 32.6% (31) females. Majority (n=29, 30.5%) patients were in the age range of 41-50years, 24.2% (n=23) in the age group of 31-40 years and 20% (n=19)in the age range of 21-30 years. Almost 70.5% (n=67) of the patients presented within 6 months of onset of their symptoms. The commonest complication after surgery was transient hoarseness in 3.2% (n=3) cases. We had post-op dysphagia and discitis each in 2.1% (n=2) patients. The overall morbiditywas 8.5% (n=8). One patient died because of anesthesia complication and not because of surgery complications.